Experimental Determination of the Current Constriction Characteristics at the Anode of AMF Vacuum Arcs - Ma, Hui; Liu, Zhiyuan; Geng, Yingsan; Wang, Jianhua; Zhang, Zaiqin; Xiao, Xiangwen (IEEE transactions on plasma science, 2019)
Before the formation of the anode spot, the anode current constriction is considered as a result of current constriction on the cathode surface and in the arc column. The objective of this paper is to quantitatively determine the current constriction characteristics by experiments at the anode of vacuum arcs under an axial magnetic field (AMF). In this paper, the radial distribution of the anode current density in a diffused vacuum arc was determined quantitatively by a novel method of four types of split-anode contacts, with various diameters of the central areas. The vacuum arc was in the diffuse arc mode with the arc current ranging from 6-to 14-kA rms. An external AMF was applied at 74 mT. The results indicate that the radial distribution of the anode current density j_{z} is in the form of the three-parameter equation, j_{z}=aj_{A}e^{(-br\wedge 2)}+c , where j_{A} is the average current density on the whole anode surface, r is the radius of the anode contact, and the value of constants a , b , and c depends on the arc current. Moreover, the results reveal the constriction characteristics of the anode current density in high-current vacuum arcs subject to the AMF, which was quite uneven in the radial distribution of the anode current density in the diffuse arc mode. Finally, under various arc currents, the constriction characteristics of the anode current density reveal similar patterns. The current density mainly constricted in the central region, in which the diameter might be only one-third of the whole diameter of the anode contact.